Design and Modeling of Tunable Band-Stop Filter Using Evanescent Mode Resonators - Hung, Shang Yu; Guo, Yu (2018 Progress in Electromagnetics Research Symposium (PIERS-Toyama), 2018)
While most of recent filter researches stress emphasis on band-pass filter that has fully-reconfigurable bandwidth, center frequency, roll-off, transmission zeros, and such; a little focus is put on band-stop type filter, thus the room for progress in such subject is more abundant In this paper, a novel band-stop type filter that utilizes resonators based on substrate-integrated waveguide (SIW) vias is introduced herein. The idea of such filter design is to mount the SIW-based resonator parallel and closely to coplanar waveguide (CPW); such CPW is designed very similar to daisy chain structure such that partial of the energy could be fed into the resonators particularly at resonant frequency. Each resonato's frequency is controlled and determined by a surface-mount capacitor. When the SIW resonator is triggered to its resonant frequency, the CPW could be regarded as short circuited yet most of the current will be drawn to the ground such that little or no signal travels through the structure, thereby a notch-like stop-band could be formed. Furthermore, the coupling between these SIW resonators could also be realized by using surface-mount capacitors along with properly designed slotlines on bottom metal, thus the bandwidth of the stop-band could be further controlled In this design, since the whole filter structure is also conductor-backed such that radiation loss could be minimized; additionally, characteristic impedance of such CBCPW line is set to be 50 Ohms, and the height of substrate is compatible to common PCB thickness and SMA connectors.